Exploring the perspectives of clinicians on solutions to tackling physical inactivity and sedentary behaviour in older hospital patients. Issue 1 (30th June 2022) - Jasper, Unyime; Visvanathan, Renuka; Dollard, Joanne; Yu, Solomon; Jadczak, Agathe Daria
Abstract: Objective: Despite growing research on sedentary behaviour and physical activity among hospitalised older people, there is little evidence of effective intervention strategies. This study sought input from clinical staff from various health professions on strategies to increase physical activity and reduce sedentariness for hospitalised older people. Methods: A 60‐minute focus group discussion involving two physiotherapists, two occupational therapists, one doctor, one nurse and one social worker was conducted. Participants were recruited from a subacute geriatric ward and an acute orthopaedic ward with an orthogeriatric service at a general hospital. Data were thematically analysed. Results: Six strategies to reduce sedentary behaviour and increase physical activity were identified: clear and positive communication for patients and family/carers; educating patients and family/carers; involving family/carers and volunteers; setting physical activity goals; utilising group activities and activities of daily living (ADL); and making the hospital environment activity‐friendly. Conclusions: This research has revealed novel strategies to increase physical activity and reduce sedentary behaviour in hospital. The next step is to design interventions for testing.